Prevalence and antibiotic susceptibility profiles of bacteria isolated from out-patients presenting with septic wounds in Kajiado county, Kenya - Kaanto, Ruth; Kagira, John M.; Waititu, Kenneth; Ngotho, Maina; Achoki, Peter H.; Gachohi, John; Maina, Naomi (International Journal Of Community Medicine And Public Health, 2026)
Background: The emergence of antibiotic resistance amongst bacteria colonizing wounds remains a serious global public health concern. There is a need for surveillance data on antimicrobial resistance, as this is critical in influencing policy on disease management. Methods: The study utilized a cross-sectional study design to select 182 patients with septic wounds attending three level 3 hospitals within Kajiado County. Samples from abscesses, burns, surgical septic wounds, and lesions from patients were collected using sterile swabs, placed in transport media and transported to the lab in cold. The samples were subjected to standard bacteriological methods for isolation, characterization and identification of bacteria isolates. Antimicrobial susceptibility test was performed using the Kirby-Bauer method. Results: The predominant bacteria isolated were Coagulase-negative Staphylococci (35.71%), S. aureus (31.69%) and E. faecalis (30.77%), P. mirabilis (19.78%), Pantoea species (14.84%) and A. viridans (12.09%). The S. aureus exhibited varied resistance to amoxicillin (20-91.9%) and ceftazidime (62.22-94.00%) but was highly susceptible to ciprofloxacin (82-97.30%) across different hospitals. Conclusions: Staphylococcus spp. were the most prevalent bacteria isolated from patients in the study area and exhibited varying patterns of antibiotic resistance, with high resistance to amoxicillin and ceftazidime and high susceptibility to Ciprofloxacin. Further studies are needed to determine the factors associated with the occurrence of antibiotic resistance in bacteria in order to develop strategies to limit the emergence and spread of resistant pathogens.